Developing-countries in the age of globalisation : regional trends and economic policy recommendations - Gottwald, Klaus; Hemmer, Hans-Rimbert; Justus Liebig University Giessen (My University, 1998)
Globalisation is a frequently used buzzword which many people associate with a fear of unemployment, rising inequality and social decline. In various instances, globalisation is even used as a scapegoat for every perceptible wrong turn; memories of the dependency debate of the seventies and eighties are reawakened. Others see globalisation as the greatest opportunity which has arisen in the few past years to transport the progress of Man to the remotest corners of the world, for the benefit of all. This evaluation of globalisation, ranging as it does over the entire conceivable spectrum between demonising and glorifying, is the reason for the attempt which has been undertaken here to take stock of the present empirical
Keywords: ddc:330